Visual Form, Video Duration, and Communication Behavior of TikTok Content on Increasing Generation Z's Knowledge of Urban Farming - Komang Tri Asta Pradnya Sulaksana (INDONESIAN JOURNAL OF SMALL SCALE FARMING, 2025)
BACKGROUND AND OBJECTIVES: Much knowledge can be easily obtained online, one of which is TikTok. Urban farming has become one of the interesting topics thanks to the support of TikTok. However, the topic of urban farming is currently not included in the category of the most favorite TikTok content watched by TikTok users. Since the entry of TikTok, the ecosystem of the content world, especially video content, has changed. In producing TikTok content, it also pays attention to visual form, video duration, and language style. Even content with a short duration is considered much more varied and adaptive. Therefore, this study aims to form a prototype of TikTok content about urban farming that is effective for increasing Generation Z's knowledge about urban farming, examine the effect of visual form, video duration, and language style of TikTok content on increasing Generation Z's knowledge about urban farming, and analyze the relationship between personal characteristics and communication behavior with increasing generation Z's knowledge about urban farming. METHODS: This research was conducted in Denpasar City. The population of this study consisted of students of State Junior High School and State Senior High School 3 Denpasar, active students of the Agribusiness Study Program, Faculty of Agriculture, Udayana University class of 2022, and members of ST. Werdhi Yowana. The sample amounted to 96 and was determined using the Slovin formula. The samples were randomly distributed into eight experimental groups and one control group. The method in this study used a true experiment with a pretest posttest control group design approach. Data analysis used paired sample t-test, chi-square, and Spearman rank using SPSS software. FINDINGS: The results of this study show that all content prototypes produced from a combination of visual forms, video duration, and language style significantly increase Generation Z's knowledge. The highest increase was obtained by combining a long-duration graphic visual form with a conversational language style. The personal characteristics of respondents did not correlate with the increase in knowledge, but communication behavior, namely exposure to communication media, correlated with the increase in respondents' knowledge. CONCLUSION: This study concludes that all combinations of visual form, video duration, and language style increase Generation Z's knowledge. Personal characteristics do not correlate with increasing knowledge, while communication behavior, namely exposure to communication media, has a significant correlation. Thus, the results of this study can be used as a reference strategy for content creators, extension workers, and the government to reach Generation Z